INFLUENCE OF HOME ENVIRONMENT ON ACADEMIC PERFORMANCE OF SECONDARY SCHOOL STUDENTS A CASE STUDY OF OYIGBO LGA OF RIVERS STATE - Ezevunwo, Obinachi Wori; Egbuchu , Samuel Aleruchi; Omobolanle, Shakirat Oshoko (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
The purpose of the study is to find out the influence of home background on the student’s academic performance Oyigbo of Rivers State. The literature review was done through reading of textbooks newspapers and journals the method adopted were the questionnaires. The data got from the questionnaires were collected into figures and percentages which are show in tabular from. The responses from the data collected revealed that the socio-economic of the parents, residence and the size of the family affects the academic performance of students. Finally, recommendations to the above influence of home background on students academic performance Oyigbo LGA are made and some of that include the following. Parents should try as much as possible to give much affection and encouragement to their children in order, which their children would be motivated which could boost their academic performance parents should have the number of children that they can easily cater for early upbringing of a child plays a vital role in (later) education of the child.